Characterization of Endothelial and Smooth Muscle Cells From Different Canine Vessels - Oosterhoff, Loes A.; Kruitwagen, Hedwig S.; van Wolferen, Monique E.; van Balkom, Bas W.M.; Mokry, Michal; Lansu, Nico; van den Dungen, Noortje A.M.; Penning, Louis C.; Spanjersberg, Talitha C.F.; de Graaf, Johannes W.; Veenendaal, Tomas; Zomerdijk, Flin; et al. (Frontiers in Physiology, 2019)
There is an increased demand for in vitro models resembling native vasculature. Several models that mimic angiogenic behavior of endothelial cells exist, but do not reflect its in vivo counterpart sufficiently. It is essential to take into account differences between vessel location and therefor to use multiple cell types including endothelial cells (ECs) and smooth vascular cells (vSMCs). The use of canine blood vessels from different vessel locations provides a way to study vasculature with similar vessel size and function compared to human vasculature. In addition, a novel isolation procedure provides the possibility to isolate both endothelial and smooth muscle cells from the same vessels. Canine primary ECs and vSMCs were isolated from the vena cava, vena porta and aorta. All tissue sources were derived from three donors for accurate comparison and to reduce inter-animal variation. Based on characterization through morphology, gene- and protein-expression and based on function, the isolation and purification of the two cell types could be confirmed. Moreover, several genes not earlier associated with vascular ECs were highly expressed in canine ECs, possibly providing candidate genes for novel EC markers. In addition, we found differences between arterial- and venous-derived endothelium based on transcriptional and functional level. As both cell types can be derived from the same vessel, this approach not only allows for accurate modelling of vascular diseases, but can ultimately be used in vascular bioreactors and tissue engineering designs. Additionally, exploring these transcriptomic and physiologic aspects of arteriovenous differentiation of primary cells has important implications for further understanding the fundamental behavior of the vasculature and pathogenesis of various vascular diseases.